Characterization of sputtered, doped BaTiO3 films for multiferroic applications - Haghighi, Sara Borhani (2009)
In this study, single phase Co-doped BaTiO3 (BTO) thin films were fabricated by magnetron sputtering on three different substrates namely, SiO2/Si, Pt/Ti/SiO2/Si and LaxSr1-xMnO3 (LSMO). The effects of sputtering parameters such as rf power, deposition pressure, oxygen content in the environment on the structure and chemistry of the films were evaluated. X-ray diffraction was used as the main characterization technique along with Rietveld refinement to obtain detailed structural and chemical information. The relationship between the film structure and sputtering parameters is the main theme of this report, but surface topography and limited ferroelectric and magnetic properties were also determined.